The implications of ergonomics factors toward work stress among new staff at Malaysia Marine and Heavy Engineering (MMHE) Sdn Bhd / Mohd Taufik Abd Samad - Abd Samad, Mohd Taufik (Faculty of Business and Management, 2010)
Ergonomics literally means the laws of work. Ergonomics refers to the complex relationship between workers and their work that permeates in every aspect of the workplace. Most of the researchers agree that work stress is caused by the workstation design or workplace environment, which is related to the ergonomics factor. This report aims to investigate and identify the Ergonomics elements that can contribute to the work stress outcome among new staff at Malaysia Marine and Heavy Engineering (MMHE) Sdn Bhd. This research will find whether Ergonomics factors such Workstation Design, Office Equipment, Office Lighting, Working Hours and Workload can lead to employee work stress at MMHE. By using all 37 items in Questionnaire, the findings highlight five Ergonomics factors that comprise Workstation Design, Office Equipment, Office Lighting, Working Hours and Workload. In determining the implication of ergonomics factors towards work stress, a Likert-type scale has been developed and tested. Therefore in this research, researcher tries to identify the implications of ergonomics factors towards work stress.